Тени исчезают в полдень: [роман] / Анатолий Иванов - Иванов Анатолий Степанович (Эксмо-Пресс, 1998)
Экземпляры: Аб (20150327) / Инвентарный номер: 102465 / Цена: 70.00 / Авт.знак: И 20 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6